Hybrid Contracts in Islamic Banking: A Shariah and Fiqh Muamalat Perspective - Supriyadi Supriyadi; Nina Kurniawati (Masyrif : Jurnal Ekonomi, Bisnis dan Manajemen, 2025)
The use of hybrid contracts in Islamic banking, where combining several contracts in one transaction is an important need in dealing with the complexity of the modern economy. The development of Islamic banking products continues to innovate to meet the community's demands. However, the hybrid contract concept often raises controversy regarding its compliance with Sharia principles. The purpose of this study is to analyze the application of hybrid contracts in Islamic banking and assess whether its application is by the provisions of Islamic law. This research uses a descriptive-analytical method with a qualitative approach, in which data is collected from primary and secondary literature relating to Islamic law and Islamic banking. The results show that product innovation through hybrid contracts contributes to the growth of the Islamic banking market. Although there are diverse views regarding the permissibility of contract combinations, this study concludes that hybrid contracts are allowed in Sharia as long as they do not contradict the basic principles of fiqh muamalah. Thus, hybrid contracts can be an important tool in the development of Islamic banking as long as they are applied carefully.